A kind of red long afterglow transparent ceramic and preparation method thereof
By adopting the chemical formula of the red long afterglow transparent ceramic is (RE1-x-y-zEuxZryMz)2O3, combined with vacuum sintering method and thermal isostatic pressing process, the problem of short afterglow time of sesquioxide long afterglow luminescent powder is solved, and the problem of short afterglow time of sesquioxide long afterglow luminescent powder is achieved Red long afterglow squioxide transparent ceramic material with high light transmittance and long afterglow time meets the performance requirements of laser devices.
Patent Information
- Application Number
- CN202310901383.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-20
- Publication Date
- 2025-01-14
- Estimated Expiration
- 2043-07-20
AI Technical Summary
The afterglow time of the sesquioxide long afterglow luminescence powder is short and cannot meet the requirements of laser devices. It lacks long afterglow quadroxide transparent ceramic materials with high light transmittance and long afterglow time.
The chemical formula of the red long afterglow transparent ceramic is (RE1-x-y-zEuxZryMz)2O3, RE is selected from Lu or Y, M is selected from Ca, Sr, Ba, and prepared by vacuum sintering method combined with thermal isostatic pressing technology, using ZrO2 As a sintering aid, thermal isostatic sintering is performed using an inert atmosphere to improve the transmittance and afterglow properties of the ceramic.
The transmittance and afterglow time of the ceramic are significantly improved, the transmittance is increased by 15 to 20%, and the afterglow time is extended by 3 to 5 hours, meeting the high light transmittance and long afterglow time of the laser device.
Smart Images

Figure CN116874301B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of transparent ceramic preparation, and in particular to a red long afterglow transparent ceramic and a preparation method thereof. Background Art
[0002] With the rapid development and wide application of laser devices, transparent ceramics as an important laser medium material have played an important role in the military, industrial production, medical and health fields. As the core component of the laser, the laser working material determines the key indicators of the laser such as output power and efficiency. Compared with single crystal materials, ceramic materials have the advantages of large-scale production, high-concentration doping, and the ability to achieve large-size and diverse composite structures. In addition, ceramic sintering technology can achieve transparency at temperatures far below the melting point of the material. Therefore, high-melting-point laser materials that are difficult to obtain with traditional single crystal growth technology can be prepared, such as sesquioxide materials, among which Yb-doped 3+ The sesquioxide ceramic material can achieve self-locking mode ultrafast laser output with a pulse width of less than 100 fs. The cubic phase structure of sesquioxide transparent ceramic RE2O3 (RE = Y, Lu) has excellent intrinsic properties (its thermo-optical properties, phonon energy, emission bandwidth, thermal conductivity and other intrinsic properties are better than garnet-based transparent ceramics), and is therefore considered to be one of the most promising new generation of high-performance solid laser medium materials.
[0003] With the improvement of ceramic technology, the structure of laser ceramic materials has become more and more diversified. Among them, long afterglow transparent ceramic materials, as a new type of laser material, have more functional characteristics than ordinary laser ceramic materials and have greater potential in laser performance. Long afterglow is a long-term delayed luminescence phenomenon of several seconds, hours or even days after the excitation of external field forces (gamma rays, X-rays, ultraviolet visible-near infrared light, electron beams, etc.) stops, relying on the excitation storage energy. The luminescence mechanism of long afterglow materials is different from that of other fluorescent materials. Its luminescence energy level is separated from the trap energy level, and it has an ultra-long metastable energy level lifetime. Long afterglow laser is a new laser working mode. By introducing long-life energy levels into the laser working material to form an "excited carrier pool", the excited carriers can stay for a long time, and release to form lasers under appropriate stimulation, realizing the separation of "stimulated absorption" and "stimulated radiation" processes. Compared with ordinary ceramic lasers, long afterglow transparent ceramic lasers can more easily control the stimulated radiation process, which promotes the miniaturization, flexibility and versatility of laser systems.
[0004] In the field of long afterglow transparent ceramics, there are currently only garnet-based long afterglow transparent ceramics, and no sesquioxide long afterglow transparent ceramics. In the research of sesquioxide long afterglow luminescent powder, Lin et al. prepared Y2O3 long afterglow luminescent powder in 98% N2-2% H2 atmosphere with Eu 3+ions as activators, co-doped with Ti 4+ or Mg 2+ ions, and a long red afterglow of nearly 1.5h was observed after excitation with 254nm light; Xie et al. prepared Y2O3:Eu by solid phase reaction method 3+ ,Ho 3+ Long afterglow luminescent powder emits bright red afterglow under ultraviolet 254nm excitation, but its afterglow time is only 10 minutes. It can be seen that the long afterglow luminescent powder of sesquioxide faces the problem of short afterglow time and cannot meet the requirements of laser. Therefore, the art urgently needs a long afterglow sesquioxide transparent ceramic with high light transmittance and long afterglow time. Summary of the invention
[0005] One of the purposes of the present invention is to provide a red long afterglow transparent ceramic with high transmittance and long afterglow time.
[0006] The second object of the present invention is to provide a method for preparing the above-mentioned red long afterglow transparent ceramic.
[0007] To achieve the above purpose, the technical solution adopted by the present invention is as follows:
[0008] In one aspect, the present invention provides a red long afterglow transparent ceramic, the general chemical formula of which is:
[0009] (RE 1-x-y-z Eu x Zr y M z )2O3,
[0010] Wherein RE is selected from Lu or Y, M is selected from one of Ca, Sr, and Ba, and the value ranges of x, y, and z are respectively: 0.05≤x≤0.5, 0.01≤y≤0.03, and 0.01≤z≤0.05.
[0011] On the other hand, the present invention provides a method for preparing the above-mentioned red long afterglow transparent ceramic, which adopts a vacuum sintering method combined with hot isostatic pressing, and specifically comprises the following steps:
[0012] (1) According to the chemical formula (RE 1-x-y-z Eu x Zr y M z )2O3, 0.05≤x≤0.5, 0.01≤y≤0.03, 0.01≤z≤0.05, respectively weighing RE2O3, Eu2O3, ZrO2, and M2CO3 with a purity greater than 99.99% as raw material powders, mixing the raw material powders, sintering aids, and ball milling media in proportion to obtain a mixed slurry;
[0013] (2) drying the mixed slurry obtained in step (1) in a drying oven, sieving the dried mixed powder, and calcining the mixed powder in a muffle furnace under air atmosphere;
[0014] (3) placing the powder calcined in step (2) into a mold for dry pressing, and then cold isostatic pressing;
[0015] (4) placing the green blank obtained in step (3) in a vacuum furnace for sintering;
[0016] (5) The ceramic obtained in step (4) is subjected to hot isostatic pressing sintering in an inert atmosphere, cooled to room temperature, and then subjected to double-sided polishing to obtain the long afterglow transparent ceramic.
[0017] Preferably, in step (1), the ball milling speed is 170-200 r / min, and the ball milling time is 10-16 h.
[0018] Preferably, in step (1), the sintering aid is ZrO2, the amount of the sintering aid added is 0.1-1% of the total mass of the raw material powder, the ball milling medium is anhydrous ethanol, and the grinding balls are ZrO2 balls.
[0019] Preferably, in step (2), the drying time is 20 to 30 hours and the drying temperature is 80 to 90°C.
[0020] Preferably, in step (2), the mesh size of the sieve is 50 to 200 meshes.
[0021] Preferably, in step (2), the calcination temperature is 600-900° C., and the calcination time is 5-8 hours.
[0022] Preferably, in step (3), the cold isostatic pressing holding pressure is 150 to 200 MPa, and the holding time is 200 to 400 s.
[0023] Preferably, in step (4), the sintering temperature is 1600-1850°C, the holding time is 8-24h, the heating rate is 5-10°C / min, the cooling rate is 3-8°C / min, and the sintering vacuum is not less than 10 -3 Pa.
[0024] Preferably, in step (5), the inert gas for hot isostatic pressing sintering is argon or helium, the pressure is 80-150 MPa, the sintering temperature is 1650-1850°C, the holding time is 2-4h, the heating rate is 8-12°C / min, and the cooling rate is 3-10°C / min.
[0025] Compared with the prior art, the present invention has the following beneficial effects:
[0026] (1) The present invention uses sesquioxide as a matrix and adopts an ion co-doping method. The transmittance of the prepared ceramic can reach about 80% at 2000nm, and the afterglow time is increased by 5 to 6 hours compared with the long afterglow material in powder form.
[0027] (2) The sintering method adopted by the present invention is a vacuum sintering method combined with hot isostatic pressing. The inert gas in hot isostatic pressing is conducive to the generation of oxygen vacancies, which can improve the transmittance and afterglow performance of the transparent ceramic. The transmittance is increased by 15-20%, and the afterglow time is increased by 3-5 hours.
[0028] (3) The present invention uses ZrO2 as a sintering aid. For long afterglow materials in powder form, the solid solubility of Ca, Sr, and Ba is limited. By doping zirconium ions inside the transparent ceramic, it is beneficial to increase the solid solubility of Ca, Sr, and Ba, and to generate oxygen vacancies. The afterglow time of the transparent ceramic is increased by 4 to 5 hours. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 It is prepared by vacuum sintering combined with hot isostatic pressing (Y 0.62 Eu 0.3 Zr 0.03 Sr 0.05 )Transmittance curve of 2O3 long afterglow transparent ceramics.
[0030] Figure 2 It is prepared by vacuum sintering combined with hot isostatic pressing (Y 0.62 Eu 0.3 Zr 0.03 Sr 0.05 )Emission spectrum of 2O3 long afterglow transparent ceramics.
[0031] Figure 3 Y 0.62 Eu 0.3 Zr 0.03 Sr 0.05 )Afterglow decay curves of 2O3 long afterglow luminescent powder and long afterglow transparent ceramics with the same composition. DETAILED DESCRIPTION
[0032] The present invention is further described in detail below with reference to the accompanying drawings and specific embodiments.
[0033] Unless otherwise stated, the raw materials used in the following examples are all commercially available products.
[0034] Example 1: Preparation (Lu 0.93 Eu 0.05 Zr 0.01 Ca 0.01 )2O3 transparent ceramic
[0035] (1) According to the chemical formula (Lu 0.93 Eu 0.05 Zr 0.01 Ca 0.01 )2O3, the raw material powder with a stoichiometric ratio of each element and a purity greater than 99.99% is 100 g in total; anhydrous ethanol is used as a ball milling medium, 40 μL of a sintering aid ZrO2 is added, the accurately weighed raw material powder is placed in a ball mill, and ZrO2 grinding balls are used to ball mill at 160 r / min for 15 hours to obtain a uniformly mixed slurry, and the ball-milled slurry is placed in an oven to dry at a drying temperature of 80°C for 28 hours. After drying, it is sieved with an 80-mesh screen and placed in a muffle furnace for calcination at 800oC for 5 hours;
[0036] (2) dry pressing the calcined powder at a pressure of 10 MPa for 180 seconds, and cold isostatically pressing at 150 MPa for 360 seconds to obtain a ceramic green body;
[0037] (3) The ceramic blank was sintered in a vacuum furnace at a sintering temperature of 1700°C, a holding time of 10 h, a heating rate of 5°C / min, a cooling rate of 3°C / min, and a sintering vacuum degree of 10 -3 Pa;
[0038] (4) The ceramics obtained by vacuum sintering are placed in a hot isostatic pressing furnace for HIP sintering, wherein the argon pressure is 80 MPa, the sintering temperature is 1650°C, the holding time is 2 h, the heating rate is 8°C / min, and the cooling rate is 3°C / min. After cooling to room temperature, double-sided polishing is performed to 2 mm to obtain the desired ceramics.
[0039] According to tests, the transmittance of the obtained transparent ceramic at 2000nm is 78%, and the afterglow time can reach 15 hours.
[0040] Example 2: Preparation (Lu 0.76 Eu 0.2 Zr 0.02 Sr 0.02 )2O3 transparent ceramic
[0041] (1) According to the chemical formula (Lu 0.76 Eu 0.2 Zr 0.02 Sr 0.02)2O3, the raw material powder with the stoichiometric ratio of each element being greater than 99.99% in total is 100 g; anhydrous ethanol is used as the ball milling medium, 60 μl of sintering aid ZrO2 is added, the accurately weighed raw material powder is placed in a ball mill, and ZrO2 grinding balls are used to ball mill at 170 r / min for 15 h to obtain a uniformly mixed slurry, the ball-milled slurry is placed in an oven to dry at a drying temperature of 82°C and a drying time of 26 h. After drying, it is sieved with a 100-mesh screen and placed in a muffle furnace for calcination at 800oC for 6 h;
[0042] (2) dry pressing the calcined powder at a pressure of 20 MPa for 90 seconds, and cold isostatically pressing at 150 MPa for 360 seconds to obtain a ceramic green body;
[0043] (3) The ceramic blank was sintered in a vacuum furnace at a sintering temperature of 1720°C, a holding time of 10 h, a heating rate of 6°C / min, a cooling rate of 4°C / min, and a sintering vacuum degree of 10 -3 Pa;
[0044] (4) The ceramics obtained by vacuum sintering are placed in a hot isostatic pressing furnace for HIP sintering, wherein the argon pressure is 90 MPa, the sintering temperature is 1700°C, the holding time is 2.5 h, the heating rate is 9°C / min, and the cooling rate is 4°C / min. After cooling to room temperature, double-sided polishing is performed to 2 mm to obtain the desired ceramics.
[0045] According to tests, the transmittance of the obtained transparent ceramic at 2000nm is 78.6%, and the afterglow time can reach 15.5 hours.
[0046] Example 3: Preparation (Lu 0.62 Eu 0.3 Zr 0.03 Ba 0.05 )2O3 transparent ceramic
[0047] (1) According to the chemical formula (Lu 0.62 Eu 0.3 Zr 0.03 Ba 0.05 )2O3, the raw material powder with the stoichiometric ratio of each element being greater than 99.99% in total is 100 g; anhydrous ethanol is used as the ball milling medium, 80 μl of sintering aid ZrO2 is added, the accurately weighed raw material powder is placed in a ball mill, and ZrO2 grinding balls are used to ball mill at 180 r / min for 15 h to obtain a uniformly mixed slurry, the ball-milled slurry is placed in an oven to dry at a drying temperature of 84°C and a drying time of 24 h. After drying, it is sieved with a 140-mesh screen and placed in a muffle furnace for calcination at 800oC for 6.5 h;
[0048] (2) dry pressing the calcined powder at a pressure of 20 MPa for 90 seconds, and cold isostatically pressing at 150 MPa for 360 seconds to obtain a ceramic green body;
[0049] (3) The ceramic blank was sintered in a vacuum furnace at a sintering temperature of 1750°C, a holding time of 10 h, a heating rate of 7°C / min, a cooling rate of 5°C / min, and a sintering vacuum degree of 10 -3 Pa;
[0050] (4) The ceramics obtained by vacuum sintering are placed in a hot isostatic pressing furnace for HIP sintering, wherein the argon pressure is 110 MPa, the sintering temperature is 1720°C, the holding time is 3 h, the heating rate is 10°C / min, and the cooling rate is 6°C / min. After cooling to room temperature, double-sided polishing is performed to 2 mm to obtain the desired ceramics.
[0051] After testing, the transmittance of the obtained transparent ceramic at 2000nm is 79%, and the afterglow time can reach 15.8 hours.
[0052] Example 4: Preparation (Y 0.62 Eu 0.3 Zr 0.03 Ca 0.05 )2O3 transparent ceramic
[0053] (3) According to the chemical formula (Y 0.62 Eu 0.3 Zr 0.03 Ca 0.05 )2O3, the raw material powder with the stoichiometric ratio of each element being greater than 99.99% in total is 100 g; anhydrous ethanol is used as the ball milling medium, 100 μL of sintering aid ZrO2 is added, the accurately weighed raw material powder is placed in a ball mill, and ZrO2 grinding balls are used to ball mill at 190 r / min for 15 h to obtain a uniformly mixed slurry, the ball-milled slurry is placed in an oven to dry at a drying temperature of 86°C and a drying time of 22 h. After drying, it is sieved with a 120-mesh screen and placed in a muffle furnace for calcination at 800oC for 7 h;
[0054] (4) dry pressing the calcined powder at a pressure of 20 MPa for 90 seconds, and cold isostatically pressing at 150 MPa for 360 seconds to obtain a ceramic green body;
[0055] (3) The ceramic blank was sintered in a vacuum furnace at a sintering temperature of 1780°C, a holding time of 10 h, a heating rate of 8°C / min, a cooling rate of 6°C / min, and a sintering vacuum degree of 10 -3 Pa;
[0056] (4) The ceramics obtained by vacuum sintering are placed in a hot isostatic pressing furnace for HIP sintering, wherein the argon pressure is 100 MPa, the sintering temperature is 1750°C, the holding time is 3 h, the heating rate is 10°C / min, and the cooling rate is 5°C / min. After cooling to room temperature, double-sided polishing is performed to 2 mm to obtain the desired ceramics.
[0057] According to tests, the transmittance of the obtained transparent ceramic at 2000nm is 80.1%, and the afterglow time can reach 16 hours.
[0058] Example 5: Preparation (Y 0.62 Eu 0.3 Zr 0.03 Sr 0.05 )2O3 transparent ceramic
[0059] (5) According to the chemical formula (Y 0.62 Eu 0.3 Zr 0.03 Sr 0.05 )2O3, the raw material powder with a stoichiometric ratio of each element and a purity greater than 99.99% is 100 grams in total; anhydrous ethanol is used as a ball milling medium, 120 μL of a sintering aid ZrO2 is added, the accurately weighed raw material powder is placed in a ball mill, and ZrO2 grinding balls are used to ball mill at 200 r / min for 15 hours to obtain a uniformly mixed slurry, and the ball-milled slurry is placed in an oven to dry at a drying temperature of 88°C and a drying time of 20 hours. After drying, it is sieved with a 140-mesh screen and placed in a muffle furnace for calcination at 800oC for 8 hours;
[0060] (6) dry pressing the calcined powder at a pressure of 20 MPa for 90 seconds, and cold isostatically pressing at 150 MPa for 360 seconds to obtain a ceramic green body;
[0061] (3) The ceramic blank was sintered in a vacuum furnace at a sintering temperature of 1800°C, a holding time of 10 h, a heating rate of 9°C / min, a cooling rate of 7°C / min, and a sintering vacuum degree of 10 -3 Pa;
[0062] (4) The ceramics obtained by vacuum sintering are placed in a hot isostatic pressing furnace for HIP sintering, wherein the argon pressure is 110 MPa, the sintering temperature is 1750°C, the holding time is 3 h, the heating rate is 12°C / min, and the cooling rate is 10°C / min. After cooling to room temperature, double-sided polishing is performed to 2 mm to obtain the desired ceramics.
[0063] Figure 1 For this example, (Y 0.62 Eu 0.3 Zr 0.03 Sr 0.05)The transmittance curve of 2O3 long afterglow transparent ceramics shows that the transmittance at 2000nm is 80.3%.
[0064] Figure 2 For this example, (Y 0.62 Eu 0.3 Zr 0.03 Sr 0.05 The emission spectrum of )2O3 long afterglow transparent ceramics has strong luminescence in the range of 600-630nm.
[0065] Figure 3 The prepared powder form (Y 0.62 Eu 0.3 Zr 0.03 Sr 0.05 )2O3 long afterglow luminescent powder afterglow decay curve, after stopping the irradiation source (ultraviolet 254nm) excitation, the afterglow time is 9 hours, the afterglow tester is used to measure the prepared (Y 0.62 Eu 0.3 Zr 0.03 Sr 0.05 )The afterglow decay curve of the 2O3 long afterglow transparent ceramic shows that the afterglow time exceeds 16 hours after the irradiation source (ultraviolet 254nm) is stopped.
[0066] The above description is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Any modifications, equivalent substitutions and improvements made by any technician familiar with the technical field within the technical scope disclosed by the present invention and within the spirit and principle of the present invention should be covered by the protection scope of the present invention.
Claims
1. A red long afterglow transparent ceramic, characterized in that: The general chemical formula of the ceramic is: (RE 1-x-y-z I x Zr y M z )2O3, Wherein RE is selected from Lu or Y, M is selected from one of Ca, Sr, and Ba, and the value ranges of x, y, and z are respectively: 0.05≤x≤0.5, 0.01≤y≤0.03, 0.01≤z≤0.05; The preparation is carried out by vacuum sintering combined with hot isostatic pressing, which specifically includes the following steps: (1) According to the chemical formula (RE 1-x-y-z Eu x Zr y M z )2O3, 0.05≤x≤0.5, 0.01≤y≤0.03, 0.01≤z≤0.05, respectively weigh RE2O3, Eu2O3, ZrO2, and M2CO3 with a purity greater than 99.99% as raw material powders, mix the raw material powders, sintering aids, and ball milling media in proportion, and obtain a mixed slurry; the sintering aid is ZrO2; (2) drying the mixed slurry obtained in step (1) in a drying oven, sieving the dried mixed powder, and calcining the mixed powder in a muffle furnace under air atmosphere; (3) placing the powder calcined in step (2) into a mold for dry pressing, and then cold isostatic pressing; (4) placing the green blank obtained in step (3) in a vacuum furnace for sintering; (5) The ceramic obtained in step (4) is subjected to hot isostatic pressing sintering in an inert atmosphere, cooled to room temperature, and then subjected to double-sided polishing to obtain the long afterglow transparent ceramic.
2. The red long afterglow transparent ceramic according to claim 1, characterized in that: In step (1), the ball milling speed is 160-200 r / min, and the ball milling time is 10-16 h.
3. The red long afterglow transparent ceramic according to claim 1, characterized in that: In step (1), the amount of the sintering aid added is 0.1-1% of the total mass of the raw material powder, the ball milling medium is anhydrous ethanol, and the grinding balls are ZrO2 balls.
4. The red long afterglow transparent ceramic according to claim 1, characterized in that: In step (2), the drying time is 20-30 hours and the drying temperature is 80-90°C.
5. The red long afterglow transparent ceramic according to claim 1, characterized in that: In step (2), the mesh size of the sieve is 50 to 200 meshes.
6. The red long afterglow transparent ceramic according to claim 1, characterized in that: In step (2), the calcination temperature is 600-900° C. and the calcination time is 5-8 hours.
7. The red long afterglow transparent ceramic according to claim 1, characterized in that: In step (3), the cold isostatic pressing holding pressure is 150-200 MPa, and the holding time is 200-400 s.
8. The red long afterglow transparent ceramic according to claim 1, characterized in that: In step (4), the sintering temperature is 1600-1850°C, the holding time is 8-24h, the heating rate is 5-10°C / min, the cooling rate is 3-8°C / min, and the sintering vacuum is not less than 10 -3 Pa.
9. The red long afterglow transparent ceramic according to claim 1, characterized in that: In step (5), the inert gas for hot isostatic pressing sintering is argon or helium, the pressure is 80-150 MPa, the sintering temperature is 1650-1850°C, the holding time is 2-4 h, the heating rate is 8-12°C / min, and the cooling rate is 3-10°C / min.
Citation Information
Patent Citations
Red light emitting material capable of being stimulated by near ultraviolet or blue light chip as well as preparation method and application thereof
CN108753296A